Elasticity evaluation of the plantar fascia: A shear wave elastography study involving 33 early-stage plantar fasciopathy subjects - Jiang, Zhen-Zhen; Shen, Hua-Liang; Zhang, Qi; Ye, Gang; Li, Xiu-Cheng; Liu, Xia-Tian (Frontiers in Physiology, 2022)
Background: Plantar fasciopathy, the most common foot condition seen in elderly and athletic populations, can be diagnosed and differentially diagnosed with imaging modalities such as ultrasound shear wave elastography (SWE). However, standard guidelines for ultrasound elastography of the plantar fascia are lacking. The purpose of this study was to determine the impact of the region of interest (ROI) on the evaluation of the plantar fascia elasticity and confirm the screening accuracy of SWE in the early-stage of plantar fasciopathy. Methods: This was an observational case‒control study involving 50 feet of 33 early-stage plantar fasciopathy subjects (the plantar fasciopathy group) and 96 asymptomatic feet of 48 healthy volunteers (the non-pain group). Clinical information, including age, gender, height, weight, visual analogue scale (VAS) score, American Orthopaedic Foot and Ankle Scale score (AOFAS), and the symptom duration, were recorded. All participants underwent both conventional ultrasound and SWE evaluation. The plantar fascia elastic parameters included SWEsingle-point, calculated with a single-point ROI set at the greatest thickness of the plantar fascia, and SWEmulti-point, calculated by multipoint ROIs set continuously from the origin at the calcaneus to about 2 cm from the calcaneal origin. Results: The plantar fasciopathy group presented a higher VAS score (median [IQR), 4.00 (3.00) vs. 0.00 (0.00), p < 0.001] and lower AOFAS score [median (IQR), 79.50 (3.00) vs. 100.00 (10.00), p < 0.001] than the non-pain group. The median plantar fascia thickness of the plantar fasciopathy group was significantly greater than that of the non-pain group [median (IQR), 3.95 (1.37) mm vs 2.40 (0.60) mm, p < 0.001]. Abnormal ultrasound features, including echogenicity, border irregularities, and blood flow signals, were more prominent in the plantar fasciopathy group than in the non-pain group (29% vs. 0%, p < 0.001; 26% vs. 1%, p < 0.001; 12% vs. 0%, p < 0.001, respectively). Quantitative analysis of the plantar fascia elasticity revealed that the difference between the value of SWEsingle-point and SWEmultipoint was significant [median (IQR), 65.76 (58.58) vs. 57.42 (35.52) kPa, p = 0.02). There was a moderate and significant correlation between the value of SWEsingle-point and heel pain. However, there was no correlation between the value of SWEmultipoint and heel pain. Finally, we utilized the results of SWEsingle-point as the best elastic parameter reflecting clinical heel pain and found that SWEsingle-point could provide additional value in screening early-stage plantar fasciopathy, with an increase in sensitivity from 76% to 92% over conventional ultrasound alone. Additionally, compared with conventional ultrasound and SWE, the use of both improved the accuracy of screening for plantar fasciopathy. Although there were no significant differences in the negative predictive value of conventional ultrasound, SWE, and their combination, the positive predictive value when using both (90.20%) was significantly greater than that when using conventional ultrasound (74.50%) or SWE alone (76.50%). Conclusion: The plantar fascia elastic parameter calculated with single-point ROIs set at the greatest thickness of the plantar fascia is positively correlated with fascia feel pain. Single-point analysis is sufficient for the screening of the early-stage plantar fasciopathy using SWE. SWEsingle-point may provide additional valuable information for assessing the severity of plantar fasciopathy.